Emerging modes of collective cell migration induced by geometrical constraints - Vedula, Sri Ram Krishna; Leong, Man Chun; Lai, Tan Lei; Hersen, Pascal; Kabla, Alexandre J.; Lim, Chwee Teck; Ladoux, Benoît (Proceedings of the National Academy of Sciences of the United States of America, 2012)
The role of geometrical confinement on collective cell migration has been recognized but has not been elucidated yet. Here, we show that the geometrical properties of the environment regulate the formation of collective cell migration patterns through cell-cell interactions. Using microfabrication techniques to allow epithelial cell sheets to migrate into strips whose width was varied from one up to several cell diameters, we identified the modes of collective migration in response to geometrical constraints. Weobserved that a decrease in the width of the strips is accompanied by an overall increase in the speed of the migrating cell sheet. Moreover, large-scale vortices over tens of cell lengths appeared in the wide strips whereas a contraction-elongation type of motion is observed in the narrow strips. Velocity fields and traction force signatures within the cellular population revealed migration modes with alternative pulling and/or pushing mechanisms that depend on extrinsic constraints. Force transmission through intercellular contacts plays a key role in this process because the disruption of cell-cell junctions abolishes directed collective migration and passive cell-cell adhesions tend to move the cells uniformly together independent of the geometry. Altogether, these findings not only demonstrate the existence of patterns of collective cell migration depending on external constraints but also provide a mechanical explanation for how large-scale interactions through cell-cell junctions can feed back to regulate the organization of migrating tissues.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell traction forces; Collective dynamics; Madin darby canine kidney epithelial cells; Particle image velocimetry